2002
DOI: 10.1308/135576102322482054
|View full text |Cite
|
Sign up to set email alerts
|

The Working Patterns and Retirement Plans of General Dental Practitioners in a Midlands Health Authority

Abstract: The findings add weight to the view that woman dentists tend to work fewer hours but studies of cohorts are required to examine the impact of premature retirement and the reasons behind this apparent gender difference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…4,7 Such surveys that have been completed suggested that between 16% and two thirds of GDPs planned to retire before they were 60. Similarly the cur rent study found 59% intended to retire from full-time dentistry before this age; however, 35% would continue to work on a part-time basis.…”
Section: Retirementmentioning
confidence: 99%
“…4,7 Such surveys that have been completed suggested that between 16% and two thirds of GDPs planned to retire before they were 60. Similarly the cur rent study found 59% intended to retire from full-time dentistry before this age; however, 35% would continue to work on a part-time basis.…”
Section: Retirementmentioning
confidence: 99%
“…Also, 34% of respondents point out that they feel mental and emotional exhaustion. As many as 83% of surveyed dentists believe that their profession is extremely stressful 23 , while almost 60% believe that the dental profession is more stressful than other professions 57 . According to Myers and huge benefits for psycho-physical conditions of dentists.…”
Section: Prevalence Of Stress Among Dentists and Recommendations For Its Reductionmentioning
confidence: 99%
“…19,20,21 With this in mind, the reported increase in the percentage of female orthodontic residents may require an increase in the number of orthodontists in the U.S. in order to meet patient needs. The median number of years between dental school and beginning orthodontic training was 1-2 years.…”
Section: Demographicsmentioning
confidence: 99%